Evidence for Psi: Thirteen Empirical Research Reports edited by Damien Broderick and Ben Goertzel - Lobach, Eva (Journal of Scientific Exploration, 2015)
One reason I love parapsychology is the colorful collection of scientists it brings together. I think few fields can boast the shared research efforts of engineers, physicists, anthropologists, psychologists, sociologists, biologists, neuroscientists, philosophers, statisticians, and many other professionals. New, exciting ideas are often born at the crossroads of different fields. The downside of so many different backgrounds is that each has its own culture and scientific jargon. This is obvious from the various chapters that are brought together in Evidence for Psi: Thirteen Empirical Research Reports introduced and edited by Damien Broderick and Ben Goertzel. Many contributors introduce their own words to describe very similar if not the same concepts. The unsuspecting reader is at risk of getting lost in a jungle of concepts and acronyms. In addition, using different words for the same thing, or the same words for different things, stands in the way of fruitful discussions among psi researchers, even more so between psi researchers and scientists in other fields, let alone discussions with skeptics. Although discussions with skeptics may be another story.